Periodic solutions of Ginzburg–Landau theory for atomic Fermi gases near the BCS–BEC crossover. Issue 4 (4th March 2022) - Guo, Boling; Pei, Yitong
ABSTRACT: In this paper, the existence of the time-periodic solution to the time-dependent Ginzburg–Landau(TDGL) equations in the case of BCS–BEC crossover is established relying on the Leray–Schauder fixed point theorem.